"Billing Yard Inspection of Nursery Stock". Issue 5 (23rd August 2014) - Drinnan, Dana E.
Abstract : This paper deals more with the different types of inspection, rather than billing yard inspection. The types of inspection may be as follows: Field, Destination and Billing Yard. The type most used is Field Inspection. The purpose of this inspection is to detect insects and diseases during the growing period and to correct them. Certificate is issued on this insepction. There are both advantages and disadvantages in this system. The inspection of Destination is made when trees or plants are delivered. Billing yard inspection is given when trees or plants are being shipped. All diseases and irregularities are checked during this inspection. Its importance cannot be overestimated. Neither of the three systems when used alone is sufficient. Best results can be obtained from combination of the three.